Exercise in Serbian language teaching in the function of improvement of primary school pupils’ oral and written expression - Purić Daliborka S. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu), 2018)
Modern society, among other things, is characterized by a kind of crisis in culture, which transposes both the culture of speech and the culture of written expression. Although the participation of the educational institutions in solving this problem is necessary, Serbian language teaching in the elementary school itself also faces numerous challenges of developing pupils’ culture of expression. Author examines the importance of exercising in Serbian language teaching in the function of developing elementary school age pupils’language culture. Research tasks concerned teachers’ experience (N = 273) in relation to types of exercises in language culture teaching in order to promote (a) oral and (b) written expression. Results of the study show that orthoepic exercises are used to the greatest extent in the function of promoting oral expression, whereby articulation exercises are dominant in the first and second grade, and accent exercises in the third and fourth grade.The most common form of written exercises in the first and second grade is dictation, while the most frequent exercises in the third and fourth grade are written essays. By shifting the focus of teaching tasks to developing linguistic and stylistic values of expression, pupils would be more likely encouraged to apply acquired knowledge in their own language practice, in oral and written expression, and in this way, their creative potentials would be more comprehensively involved, in the function of promoting language literacy.